Analysis of Demand and the Worthiness of Investment in Electric Vehicle Taxi Service Businesses under the Taxi VIP Project of the Department of Land Transport in Digital Economy Era - Chuenjai, Ratchada; Chomtohsuwan, Thoedsak (Journal of Humanities and Social Sciences Thonburi University, 2021)
The objective of this study was to investigate the demand for service and the worthiness of investment in the electric taxi service business under the Taxi VIP project by the Department of Land Transport. This study was conducted by estimating the demand equation, price elasticity of demand, and income elasticity of demand. Primary data was collected from the sample of 400 electric taxi consumers through interviews. To assessing the worthiness of investment, cost-benefit analysis was conducted based on the secondary data on the operations of the electric taxi service business. The results of this study indicated that using the electric taxi service had a high price elasticity of demand and income elasticity of demand. The findings indicated that the foresaid electric taxi service is luxury goods with a high substitution rate. In addition, the project is worth investing as reflected by financial ratios as follows: a net present value (NPV) of 12.76 million baht, an internal rate of return (IRR) of 16.95%, and a payback period within 6 years and 10 months. Moreover, in this project, positive externalities could help reduce greenhouse gas.